2015
DOI: 10.1016/j.yjmcc.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant stress promotes disease by activating CaMKII

Abstract: CaMKII is activated by oxidation of methionine residues residing in the regulatory domain. Oxidized CaMKII (ox-CaMKII) is now thought to participate in cardiovascular and pulmonary diseases and cancer. This invited review summarizes current evidence for the role of ox-CaMKII in disease, considers critical knowledge gaps and suggests new areas for inquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 60 publications
0
68
0
1
Order By: Relevance
“…Increased systemic and atrial myocardial oxidative stress is often observed in post-operative patients with new onset (acute) paroxysmal AF (POAF) [3,4] with an incidence of up to 50% [5]. Diverse etiological factors such as fibrosis [6,7] and increased Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) activity [8,9] among others, are thought to play a key role in the initiation of oxidative AF [4,10]. While the causative and signaling factors of oxidative AF are reasonably well identified, the mechanism of spontaneous initiation (i.e., not induced by electrical stimulation) of acute oxidative AF in experimental and human studies, remains undefined [10].…”
Section: Introductionmentioning
confidence: 99%
“…Increased systemic and atrial myocardial oxidative stress is often observed in post-operative patients with new onset (acute) paroxysmal AF (POAF) [3,4] with an incidence of up to 50% [5]. Diverse etiological factors such as fibrosis [6,7] and increased Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) activity [8,9] among others, are thought to play a key role in the initiation of oxidative AF [4,10]. While the causative and signaling factors of oxidative AF are reasonably well identified, the mechanism of spontaneous initiation (i.e., not induced by electrical stimulation) of acute oxidative AF in experimental and human studies, remains undefined [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there was a significant relationship between necrotic area and p-CaMKII MFI per total lesion area (Supplemental Figure 1B). Given the role of CaMKII in smooth muscle cells (11,19), we compared p-CaMKII MFI associated with smooth muscle α-actinpositive (SMαA-positive) cells in lesions and found no significant differences between the plaques of asymptomatic and symptomatic patients (Supplemental Figure 1C). Thus, although CaMKII is active in both macrophages and smooth muscle cells in atherosclerosis, it is primarily the activity in macrophages that increases in symptomatic lesions.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms that contribute to defective efferocytosis in advanced atherosclerosis, however, have not yet been fully elucidated. Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) is a serine-threonine kinase that is a key mediator of Ca 2+ -regulated processes in many different cell types (11,12). There are 4 CaMKII isoforms, α, β, δ, and γ, each encoded by a distinct gene.…”
Section: Introductionmentioning
confidence: 99%
“…ox-CaMKII has recently been considered to be a critical mechanism linking ROS and downstream asthma phenotypes (9). Previous studies found that ox-CaMKII was significantly increased in the airway epithelium of asthmatic patients and correlated with asthma severity (18).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of the airway epithelium to environmental pollutants or allergens is known to induce oxidative stress either directly or through the induction of local inflammatory processes that lead to the secondary production of ROS (6)(7)(8). Previous studies suggest that the multifunctional Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) is within one of the downstream signaling pathways activated by ROS (9). CaMKII has four isoforms, α, β, δ, and γ, encoded by different genes, displaying distinct but overlapping expression patterns (10).…”
Section: Introductionmentioning
confidence: 99%